Relationship Between Mutans Streptococci and Lactobacilli in the Oral Cavity and Intestine of Obese and Eutrophic Children With Early Childhood Caries—Preliminary Findings of a Cross-Sectional Study - Indiani, Claudia Maria dos Santos Pereira; Rizzardi, Karina Ferreira; Crescente, Camila Lopes; Steiner-Oliveira, Carolina; Nobre-dos-Santos, Marinês; Parisotto, Thaís Manzano (Frontiers in Pediatrics, 2020)
This brief communication assessed whether there was any relationship between the counts of lactobacilli (LB) and mutans streptococci (MS) in the oral cavity and intestine of obese and eutrophic children with early childhood caries (ECC). Seventy-eight preschoolers were assigned into the following groups: 1. obese children with ECC (OECC); 2. eutrophic children with ECC (EECC); 3. obese caries-free children (OCF); and 4. eutrophic caries-free children (ECF). The diagnosis of obesity and ECC were based on the World Health Organization criteria. Dental plaque and fecal samples were collected to assess the counts of MS and LB using selective media. Data were evaluated by Poisson regression analysis, Wilcoxon test and Sign test. Microbial indicators of ECC in obese children were MS counts in the intestine (rate ratio [RR]: 4.38) and presence of LB in the oral cavity (RR: 2.12). The indicators in eutrophic children were MS levels and the presence of LB, both in the oral cavity (RR: 6.35/1.50) and intestine (RR: 2.35/2.38) (p<0.05). The comparison between MS levels in the mouth and in the intestine revealed significant differences only in the ECF group (p=0.04). Regarding LB presence in the mouth versus in the intestine, except for the OCF group (p=0.03), no others statistical differences were found. Our preliminary findings highlighted that the levels of MS and the presence of LB in the oral cavity, as well as in the lower gastrointestinal tract were associated with ECC. Moreover, obesity was found to influence this relationship.